Surgical Safety Checklist: Documentation of Use of Electrocautery and Tourniquet Devices - Fatemeh Maraki; Ahmad Ghadami; Mohammadreza Zarei; Negin Larti (Kurdistan University of Medical Sciences, 2018)
Background & Aim: Documentation of cares is one of the responsibilities of operating room nurses. One of the possible patient damages caused during surgery is use of electrocautery and tourniquet devices. Despite the need for recording the performance of these devices, there is no specific part on surgery checklists dedicated to this issue. Therefore, this study aimed to change the safe surgery checklist through documenting the application of electrocautery and tourniquet devices. Materials & Methods: This action research was conducted on 30 operating room nurses in Isfahan, Iran in 2017. The solution of choice was adding a researcher-made checklist to the operating room files in order to document the use of electrocautery and tourniquet devices for three months. In addition, a researcher-made survey on the status of operating room file documentation was filled by the subjects before and after the intervention. Moreover, data analysis was performed in SPSS version 22 using descriptive and analytical statistics. Results: In this research, 28 out of 30 participants had a mean work experience of 11.87±8.30 years in operating rooms. Furthermore, there was a significantly higher frequency of positive response to the question of “Do you think that the checklist is useful?” after the intervention, compared to before the intervention (P<0.001). In total, 90% of the nurses agreed with adding the checklist to patient records, and 96.7% confirmed the effectiveness of the new checklist on decreased professional errors and patient damage. Conclusion: According to the results of the study, the checklist of use of electrocautery and tourniquet devices was useful. It seems that full documentation can reduce the possibility of errors and provide a valid document for healthcare providers when faced with legal problems.